Pride and Humility: semantic analysis of virtues and their antipodes (Slavic Studies, 2024)
The aim of our research was the semantic field of the virtue dignity, with lexemes that are related and opposed to it (pride, ugly, beautiful, calm, humility, modest). Since this concerns a virtue, the analysis was performed in a philosophical-theological context. We also took into account the etymological analysis of the lexemes and the implications of their etymology in terms of semantics and vocabulary enrichment. The analysis was performed based on the use of the lexemes from this semantic field within the contexts of contemporary Macedonian language and literature.